2020
DOI: 10.1177/1046496420915243
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Leader Networking Behaviors and Vertical Faultlines on Support for Innovation

Abstract: Leader networking behaviors for innovation (LNBI) is an important yet less studied topic in innovation research. This study investigates the behavioral cascading effect of LNBI on organizational support for innovation. Building on faultline theory and the demographic representativeness approach, we conceptualize vertical faultlines as demographic misalignment across job ranks, and hypothesize their moderating effects on the relationships between LNBI and organizational support for innovation. Results from a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 87 publications
1
6
0
Order By: Relevance
“…The impact of these faultlines on psychological distance and intra-subgroup reciprocity was also limited at this early stage. This finding corresponds to those of Chung et al (2020) , Calabrò et al (2021) , and other scholars.…”
Section: Resultssupporting
confidence: 91%
“…The impact of these faultlines on psychological distance and intra-subgroup reciprocity was also limited at this early stage. This finding corresponds to those of Chung et al (2020) , Calabrò et al (2021) , and other scholars.…”
Section: Resultssupporting
confidence: 91%
“…For example, organizational support for innovation (OSI), namely 'the expectation, approval, and practical support of attempts to introduce new and improved ways of doing things in the work environment' [69] (p. 28), seems to be a key factor that can facilitate the adoption of new technologies [38]. Indeed, some studies found significant relationships among OSI and the usefulness/ease of use of technology [69][70][71][72], as well as intention to use [73]. On the contrary, a lack of organizational support can undermine the company's efforts to introduce new technology [38,74].…”
Section: Organizational Variablesmentioning
confidence: 99%
“…They conceptualized faults as cross-job demographic dislocations and used data from a sample of 55 work units in a U.S. high-tech company to support a mediation model. In this model, the network behavior of senior leaders influenced innovativeness at the unit level through the network behavior of junior leaders [15].…”
Section: A Faultlinesmentioning
confidence: 99%